PENGARUH PERCEIVED USEFULNESS DAN TRUST TERHADAP MINAT MENGGUNAKAN KEMBALI E-WALLET DANA: (Studi Pada Mahasiswa Kota Medan) - Ramadhani, Suci; Siregar, Onan Marakali (Transpublika Publisher, 2022)
The majority of the current rise in DANA users are students whose lives are closely linked to information technology and Fintech. The number of e-wallets that offer attractive services currently raises considerations from consumers to reuse these services by taking into account factors such as perceived usefulness and trust. This research aimed to analyze how the effect of perceived usefulness and trust on the students’ intention to reuse DANA E-Wallet on student in Medan City. The research method used in this research was quantitative associative approach. Students’ user of DANA E-Wallet were the population of this research. The sample were 100 respondents by using purposive sampling technique. Data collecting technique used in this research was primary data which was obtained from google form. The findings showed that Perceived Usefulness had positive significant effect on the user intention with a significant value was 0.014>0.05. Trust also had a positive significant effect on the users’ intention, with a sig value was 0.000<0.05. Besides, all independent variables in the simultaneous test had influenced effect with 47.3% level, whereas 52.7% was influenced by external factors beyond this research model.